The δ18O stratigraphy of the Hoxnian lacustrine sequence at Marks Tey, Essex, UK: implications for the climatic structure of MIS 11 in Britain. (16th March 2016) - Tye, G. J.; Sherriff, J.; Candy, I.; Coxon, P.; Palmer, A.; McClymont, E. L.; Schreve, D. C.
ABSTRACT: Marine Isotope Stage 11 (MIS 11) is considered one of the best analogues for the Holocene. In the UK the long lacustrine sequence at Marks Tey, Essex, spans the entirety of the Hoxnian interglacial, the British correlative of MIS 11c. We present multiproxy evidence from a new 18.5‐m core from this sequence. Lithostratigraphy, pollen stratigraphy and biomarker evidence indicate that these sediments span the pre‐, early and late temperate intervals of this interglacial as well as cold climate sediments that post‐date the Hoxnian. The δ 18 O signal of endogenic carbonate from this sequence produces several clear patterns that are interpreted as reflecting the climatic structure of the interglacial. As well as providing evidence for long‐term climate stability during the interglacial and a major post‐Hoxnian stadial/interstadial oscillation the δ 18 O signal provides strong evidence for abrupt cooling events during the interglacial itself. One of these isotopic events occurs in association with a short‐lived increase in non‐arboreal pollen (the NAP phase). The results presented here are discussed in the context of other MIS 11 records from Europe and the North Atlantic, particularly with respect to our understanding of the occurrence of abrupt climatic events in pre‐Holocene interglacials. Copyright © 2016 The Authors. Journal of Quaternary Science Published by John Wiley & Sons Ltd.